Computerised protocols for laboratory investigation and their effect on use of medical time and resources. Issue 7 (July 1992) - Mutimer, D; McCauley, B; Nightingale, P; Ryan, M; Peters, M; Neuberger, J
Abstract : AIMS: To devise a computerised management system protocol which not only proposes the laboratory investigations to be performed on each patient but also performs related clinical functions. METHODS: The system was designed by senior members of staff. The protocols defined all laboratory investigations including haematology, biochemistry, immunology and cross-matching, and included static and dynamic rules. Patients can be changed to different or additional protocols, as required; likewise proposed tests can be deleted or added. The software is written in MUMPS and runs on a 386 PC running MSM MUMPS under MSDOS. RESULTS: The number of clinical chemistry tests requested per patient per day fell by 9.5% (p less than 0.01) for transplant recipients and by 28.8% (p less than 0.01) for non-transplant recipients. The average time spent by junior medical staff requesting laboratory investigations and enquiring about results fell from 10 minutes per patient per day to 4.1 minutes (p less than 0.001). CONCLUSIONS: The introduction of this system in no way abrogates clinicians' responsibility for the management of patients, because all proposed investigations must be confirmed or modified by the authorising doctor. The system allows for the audit of requesting patterns and subsequent improvement in protocols by recording any alterations made to the proposed investigations. Significant benefits in terms of better use of house officer time and medical resources were also achieved.